Pembrolizumab monotherapy versus pembrolizumab plus chemotherapy in patients with non‐small‐cell lung cancer: A multicenter retrospective trial. Issue 2 (5th December 2021) - Matsumoto, Hiromi; Kobayashi, Nobuaki; Somekawa, Kohei; Fukuda, Nobuhiko; Kaneko, Ayami; Kamimaki, Chisato; Kubo, Sousuke; Tanaka, Katsushi; Tagami, Yoichi; Teranishi, Shuhei; Watanabe, Keisuke; Horita, Nobuyuki; et al.
Abstract: Background: Pembrolizumab alone or in combination with chemotherapy is a standard treatment for patients with non‐small‐cell lung cancer (NSCLC) with high programmed death‐ligand 1 (PD‐L1) expression. However, no study has compared the efficacies of these two regimens. Therefore, we aimed to compare the efficacy of pembrolizumab alone and in combination with chemotherapy in NSCLC patients with high PD‐L1 expression. Methods: We conducted a multicenter retrospective trial involving patients with diagnosed unresectable or recurrent NSCLCs who had received pembrolizumab with or without chemotherapy in the first‐line setting. Patients were divided into monotherapy and combination therapy groups. The progression‐free survival (PFS), overall survival (OS), and response rate (RR) were analyzed and compared between the groups. Clinical characteristics of patients were analyzed to assess their possible relationship with treatment outcomes. Results: We enrolled 96 patients from five hospitals. Of these, 47 and 49 patients received monotherapy and combination therapy, respectively. The median PFS was 343 and 328 days in the monotherapy and combination therapy groups, respectively (hazard ratio 1.003, p = 0.99). No statistically significant differences were observed in the OS and RR between the two groups. However, in patients with metastases to the liver, lung, adrenal glands, bone, or lymph nodes, the PFS was longer in the monotherapy group than in the combination therapy group. Conclusion: Although the PFS, OS, and RR were not significantly different between patients treated with pembrolizumab alone and or with pembrolizumab in combination with chemotherapy, patients with NSCLC having metastases to specific sites may benefit more from monotherapy. Abstract : We conducted a multicenter retrospective trial involving patients with diagnosed unresectable or recurrent non‐small‐cell lung cancer who had received pembrolizumab with or without chemotherapy in the first‐line setting. The median progression‐free survival (PFS) was 343 and 328 days in the monotherapy and combination therapy groups, respectively (a). In patients with metastases to the liver, lung, adrenal glands, bone, or lymph nodes, the PFS was longer in the monotherapy group than in the combination therapy group (b).